Karakteristik Sifat Fisik dan Sensoris Mie Basah Berbahan Baku Tepung Sukun (Arthocarpus altilis fosberg) dan Tepung Ubi Jalar Ungu (Ipomea batatas I) - Deanira Fransiska Pontoluli; Jan R. Assa; Christine F. Mamuaja (Universitas Sam Ratulangi, 2017)
ABSTRACTBread fruit (Arthocarpus altilis fosberg) is a one fruit that contains a high carbohydrat that28,2g / 100 g mature flesh which is very potential to be develop as an alternative to making of varieties of noodle such as fresh noodle. Sweet potatoes in addition to containing high carbohydrates also have high anthocyanin pigment than other type of sweet potatoes. One of the processing of breadfruit and purple sweet potatoes can be used as fresh noodle. The purpose of this research is to evaluating physical characteristics and panelist preferences level. The research was designed by Randomized Block Design in five factor A (80% Bread fruits flour : 20% Sweet potatoes flour) B (70% Bread fruits flour : 30% Sweet potatoes) C (60% Bread fruits flour : 40% Sweet potatoes) D (50% Bread fruits flour : 50% Sweet potatoes) E (100% Wheat flour as a control). The analyzed parameters are level of panelist acceptance, cooking lose, water absorption, elasticity, and water content. The result of physical testing on fresh noodle to cooking lose got the averange value 3,60%, water absorption the averange valeu 6,26%, elasticity the averange value 2,42% and water content 19,29%. whereas in the averange organoleptic test the panelists give the value of neutral to dislike the fresh noodle made from breadfruit flour and sweet potato flour.Keywords: bread fruit, sweet potatoes, noodle